Direct neuro-AVC modelling and control strategy for vibration suppression of a flexible plate structure - Mat Darus, Intan Zaurah; Tokhi, M. O. (2003)
This paper investigates the development of a direct neuro-active vibration control (AVC) mechanism for vibration reduction of a flexible plate structure. A multi layer perceptron (MLP) neuro-controller is designed to characterise the ideal controller characteristic using an online adaptation and training mechanism. The effectiveness of the MLP neurocontroller is then verified within the AVC system. The neuro-AVC algorithm thus developed is implemented within a flexible plate simulation environment and its performance in the reduction of deflection at the centre of the plate is assessed. The validation of the algorithm is presented in both the time and frequency domains. Investigations reveal that the developed direct neuro-AVC controller perform very well in the suppression of vibration of a flexible plate structure.